Concept of Spiritual Wellbeing in End-of-Life Patients in Emergency Settings: A Literature Review - Weny Murni; Christina Nur Widayati; Karyanti Karyanti; Dyah Winarni; Sukasmi Sukasmi; Satriya Pranata; Siti Aisah; Aric Vranada (Pancasakti Journal Of Public Health Science And Research, 2025)
Spiritual Wellbeing (SWB) is essential in palliative care for end-of-life (EoL) patients. However, its implementation in emergency settings is often overlooked despite the significant spiritual needs of patients at the end of life. This study aims to describe and explain the concept of SWB in EoL patients in the Emergency Setting. The study used a qualitative approach based on concept analysis of the literature. Data were collected from 18 relevant articles purposively selected from international databases (2020-2024). The analysis focused on the attributes, antecedents, and consequences of SWB through thematic evaluation and cross-referencing. The results showed that four main attributes of SWB were identified: relationship with higher power, inner peace, meaning of life, and active role of family and health workers. Antecedents of SWB included clergy and family support, while consequences included improved patient quality of life and reduced anxiety. These findings demonstrate the importance of integrating spiritual care into emergency setting practice. Holistic collaboration between patients, families and healthcare professionals is key to improving the spiritual wellbeing of EoL patients.